2019
DOI: 10.28945/4358
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Sharing Process and Innovation Success: Evidence from Public Organisations in Southern Nigeria

Abstract: Aim/Purpose: This study investigates the relationship between knowledge sharing process and innovation success with specific emphasis on tacit knowledge. Based on the literature review, we hypothesised that knowledge donating and collecting have a positive relationship with innovation success. Methodology: The hypotheses were empirically tested using the partial least square path modelling with data collected from twelve state-owned public organisations operating in Southern Nigeria. Contribution: The resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
1
4
0
1
Order By: Relevance
“…The study found that EV enhances the KOL-innovation relationship. This finding is consistent with the assertions in Ononye and Igwe (2019) and Ononye (2021) that leadership behaviours that facilitate and support KS can influence cognitive processes connected to innovation. In a social exchange relationship, employees' engagement in extra-role behaviour, like EV and innovation, maybe a cognitive response to the behaviours encouraged and supported by KOL.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The study found that EV enhances the KOL-innovation relationship. This finding is consistent with the assertions in Ononye and Igwe (2019) and Ononye (2021) that leadership behaviours that facilitate and support KS can influence cognitive processes connected to innovation. In a social exchange relationship, employees' engagement in extra-role behaviour, like EV and innovation, maybe a cognitive response to the behaviours encouraged and supported by KOL.…”
Section: Discussionsupporting
confidence: 92%
“…The multicollinearity test was performed using the variance inflation factor (VIF) to establish whether the self-reported scale is free of common method bias (Hosseini & Ferreira, 2023). This is critical in ensuring that latent constructs are perfectly correlated and that reliable inferences can be drawn from the measurement model (Ononye & Igwe, 2019). Following the recommendation in Kock (2015) that a model has no problem with common method bias (CMB) if all VIF values are ≤3.3, the resulting values demonstrated that CMB does not pose a challenge in this model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the dimensions of the innovation institutions consist of policy support for innovation cultures, innovation training, recognition, and rewards (Moussa et al, 2018). To sustain innovation, human resources competencies can be improved by sharing knowledge between the public and private sectors (Ponsiglione et al, 2018) through assignment programs, mentorships, workshops, seminars, and training (Ononye & Igwe, 2019). A study in an African context recommended knowledge sharing in the public sector in collaboration with other sectors (Ononye & Igwe, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Untuk mengobservasi objek penelitian, peneliti langsung terjun ke lokasi, termasuk ikut melakukan shalat berjamaah di lokasi penelitian. Sedang wawancara, Peneliti menggunakan wawancara langsung dan via handphone, namun demi menghindari hal-hal yang tidak diinginkan, peneliti hanya mewawancarai pihak Jamaah Tabligh (Heman Ononye & Igwe, 2019). Peneliti tidak mewawancarai pihak Jamaah lain yang non-Tabligh karena dipastikan mereka akan merujuk kepada Surat Keputusan DKM yang tertanggal 8 September 2016 yang lembarannya ditempel di jendela depan Masjid al-Amin.…”
Section: Metodeunclassified